2021
DOI: 10.1177/19476035211011503
|View full text |Cite
|
Sign up to set email alerts
|

Medial Opening Wedge Proximal Tibial Osteotomy: Lessons Learned from a Series of 175 Consecutive Cases

Abstract: Introduction High tibial osteotomy (HTO) is a surgical procedure aimed at inhibiting the progression of osteoarthritis of the knee joint. The aim of this study was to identify factors influencing the functional outcome after opening wedge valgus HTO. Methods A total of 175 cases (155 patients) of varus-correcting high tibial open-wedge osteotomies using the Tomofix plate were reviewed retrospectively. Patients answered the Knee Injury and Osteoarthritis Outcome Score (KOOS) questionnaire and 4 survey follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…However, overcorrection or undercorrection was not associated with clinical outcomes. 28 , 29 Kanto et al 14 identified that a postoperative WBLR of 51.6% ± 8.4% improved outcomes after OWHTO among patients with knee OA who desired to continue sporting activities, producing a Tegner activity score ≥5 points after surgery. Saragaglia et al 13 proposed that a neutral knee axis should be the target alignment for patients who practice sports such as running, tennis, jogging, and football.…”
Section: Discussionmentioning
confidence: 99%
“…However, overcorrection or undercorrection was not associated with clinical outcomes. 28 , 29 Kanto et al 14 identified that a postoperative WBLR of 51.6% ± 8.4% improved outcomes after OWHTO among patients with knee OA who desired to continue sporting activities, producing a Tegner activity score ≥5 points after surgery. Saragaglia et al 13 proposed that a neutral knee axis should be the target alignment for patients who practice sports such as running, tennis, jogging, and football.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies were published reporting on the outcomes and complications of MOWHTO [3,4,10,17,23]. Despite the fact that many of these studies are from high-volume centres, one of the repeatedly observed limitations is the relatively small sample size of these series.…”
Section: Introductionmentioning
confidence: 99%